Spatial-Temporal Analysis of Land Cover Change and Oil Palm Expansion in Gunung Mas - Andini, Putri; Nurlika, Rahayu; Salma, Yuriduna; Wicaksono, Arditya (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2023)
Abstract: The area of oil palm plantations in Indonesia has increased over time. The growth of oil palm plantations even exceeds the percentage of the area of paddy fields, especially in Gunung Mas Regency. This phenomenon is accompanied by the implementation of